Bioresponsive polymers - Kwok, Ka Po (2014)
Certain characteristic of an appropriate hydrogel is required in bio-printing technology which includes fast gelation time with crosslinking mechanism. The natural hydrogels face problems such as batch-to-batch differences while the synthetic hydrogels do not possess necessary biological function. In order to combine the favorable properties of natural and synthetic hydrogels, hybrid hydrogels are generally considered to be a better option. Currently, wide ranges of biointeractive hydrogels are available but not all hydrogels can be used as printable bio-paper for living cells aggregates. Thus this project was conducted to improve nature of the EDC-crosslinked gelatin-PLGA hydrogel and to evaluate its suitability in bio-printing technology. EDC was used to cross-link gelatin and PLGA through forming amide bond between amino groups of gelatin and carboxyl groups of PLGA. Three studies had been conducted to meet this objective, raman spectroscopy, measurement of gelation time and rheological analysis. In the first investigation, spectroscopy study was conducted on PLGA. The results showed that the sample spectrum matched the PLGA reference spectrum. In the second investigation, all samples except the negative control managed to crosslink with EDC successfully to synthesise bio-responsive hybrid polymers which showed as the EDC concentration increased, the gelation time decreased. In the next investigation, the results showed that the hydrogel ranged from 20mg/mL to 100mg/mL EDC generally exhibited a strong shear thinning behavior. As the EDC concentration increased further, the zero-shear viscosity increased drastically. The hybrid bioresponsive hydrogel of gelatin and PLGA is a promising hydrogel to be used in biomedical field.